Relationship Between Catechol-O-Methyltransferase Polymorphism and Vitiligo in A Sample of Iraqi Peoples (Iraqi Journal of Medical Sciences, 2024)
Background: Vitiligo is a common condition, highly distributed in Iraq and in the world. It is an acquired disorder of the skin and mucous membranes. It may appear at any age; cases have been reported as early as 6 weeks after birth. Segmental vitiligo often occurs in a dermatomal pattern, This observation led to a neural hypothesis that proposes certain chemical mediators released from nerve endings may cause decreased melanin production, elevated neuropeptide levels have been demonstrated in skin affected by vitiligo.Objective: To shed light on some demographic parameter and detect the association between vitiligo and Catechol-O-Methyltransferase (COMT) gene polymorphisms in a sample of Iraqi population.Methods:This case-control study was performed to detect the polymorphism of COMT 158 G/A by polymerase chain reaction restriction length polymorphism trial in 110 individuals of two groups of peoples, the first group represent the patients and the other group was apparently healthy as control, with age range from 3-62 years. Ninety-six Iraqi vitiligo patient were selected from vitiligo patients attended the Consulting Clinic of Al-Mussyab Hospital and private clinic of dermatology in Al-Mussyab City during the period from the beginning of June 2014 till ending of September 2014. Approximately 2 ml of blood samples were collected from all individuals in ethylenediaminetetraacetic acid (EDTA) anticoagulant tubes with aseptic technique and kept in -20°C. Results: The demographic study revealed that the disease was appeared in females 59 (61.46%) more than that in males 37 (38.54%) with a highly significant difference (P ?0.01) and the ratio of females to males was 1.59: 1. The mean age of the patient group was 20.67±13.36 years with age range 3-62, the highest number of patients affected by vitiligo was found in the age range 10-19 years with a highly significant difference (P
Keywords: Vitiligo; Catechol Omethyl transferase gene; polymerase chain reaction